Kinetics and Mass Transfer Study of Oleic Acid Esterification over Prepared Nanoporous HY zeolite - Abbas, Ammar S.; Albayati, Talib M.; Alismaeel, Ziad T.; Doyle, Aidan M. (Iraqi Journal of Chemical and Petroleum Engineering, 2016)
A mathematical model was proposed to study the microkinetics of esterification reaction of oleic acid with ethanol over prepared HY zeolite catalyst. The catalyst was prepared from Iraqi kaolin source and its properties were characterized by different techniques. The esterification was done under different temperature (40 to 70˚C) with 6:1 for molar ratio of ethanol to oleic acid and 5 % catalyst loading.   The microkinetics study was done over two period of time each period was examined individually to calculate the reaction rate constant and activation energy. The impact of the mass transfer resistance to the reactant was also investigated; two different studies have been accomplished to do this purpose.   The effect of the external mass transfer resistance was studied by exploring different stirring speed (400 to 800 rpm). The results show that, the oleic acid conversion increase with increasing the stirring speed until reached 600 rpm, after this rpm the conversion doesn’t increase significantly, which mean that, the effect of external mass transfer resistance was eliminated. The activation energy for the first period is equal to 41.84 kJ/mol while in the second period is equal to 52.03 kJ/mol. The Thiele modulus calculation results show that there is no effect of mass transfer on the reaction inside the catalyst pores.